YAP1-MAML2-Rearranged Poroid Squamous Cell Carcinoma (Squamoid Porocarcinoma) Presenting as a Primary Parotid Gland Tumor - Agaimy, Abbas; Stöhr, Robert; Tögel, Lars; Hartmann, Arndt; Cramer, Thomas (Head and Neck Pathology, 2020)
Porocarcinoma (synonym: malignant eccrine poroma) is a rare aggressive carcinoma type with terminal sweat gland duct differentiation. The squamous variant of porocarcinoma is even less frequent and might be indistinguishable from conventional squamous cell carcinoma (SCC). We herein describe the first case of a carcinoma presenting as a primary parotid gland malignancy in a 24-year-old male without any other primary tumor. Total parotidectomy and neck dissection were performed followed by adjuvant chemoradiation. The patient remained alive and well 10 months after diagnosis. Histology showed keratinizing SCC infiltrating extensively the parotid gland with subtle poroid cell features. Oncogenic HPV infection was excluded by DNA-based testing. NGS analysis using the TruSight RNA fusion panel (Illumina) revealed a novel YAP1-MAML2 gene fusion. This gene fusion was reported recently in a subset of cutaneous porocarcinoma and poroma. This case of poroid SCC (or squamoid porocarcinoma) adds to the differential diagnosis of SCC presenting as parotid gland tumor and highlights the value of molecular testing in cases with unusual presentation.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Head and neck; MAML2; Parotid; Porocarcinoma; Poroma; Salivary glands; Squamous cell carcinoma; YAP1